Motion Planning for Mobile Manipulators Based on an Improved A* Algorithm and Manipulability - Cao Yi; Zhu Boyu; Gu Chao; Zhao Zhihua; Guo Yinhui (Jixie chuandong)
To address the problems of long planning time and poor operability of pick-and-place (PAP) movement of a mobile manipulator in an indoor environment, an enhanced regular A* algorithm was proposed to determine the optimal docking position and perform system motion planning, using manipulator operability as the evaluation criterion. Firstly, on the basis of conventional A* algorithm, eight search directions were simplified to five to improve the search efficiency. At the same time, a new heuristic search function was designed, and Floyd algorithm was introduced into the A* algorithm to increase the smoothness of the path. The simulation results show that the running time of the improved A* algorithm is shortened by 59.1%, the path length was reduced by 3.5%, and the number of search nodes is reduced by 41.6%. Secondly, according to the reachable workspace and Jacobian matrix of the manipulator, the maneuverability of the mobile manipulator in different positions near the target object to be PAP was evaluated, and the docking position was optimized to improve the maneuverability of the PAP movement. Finally, a mobile manipulator system consisting of a DIY six-degree-of-freedom (DOF) manipulator and Turtlebot2 mobile platform was employed to conduct comprehensive motion planning experiments in indoor environment, which verifies the effectiveness and reliability of the proposed method.